Approximating Free‐form Geometry with Height Fields for Manufacturing. (May 2015) - Herholz, Philipp; Matusik, Wojciech; Alexa, Marc
Abstract We consider the problem of manufacturing free‐form geometry with classical manufacturing techniques, such as mold casting or 3‐axis milling. We determine a set of constraints that are necessary for manufacturability and then decompose and, if necessary, deform the shape to satisfy the constraints per segment. We show that many objects can be generated from a small number of (mold‐)pieces if slight deformations are acceptable. We provide examples of actual molds and the resulting manufactured objects.